Impact of perception, attitude, and behavior on cyber resilience towards online fraud threats among IIUM students - Jamalluddin, Nur Hafifah; Wok, Saodah; Tengku Azzman, Tengku Siti Aisha; Sedu, Nerawi (Malaysian Association of Communication Educators (MACE), 2022)
Students are active users of the online platforms using it for academic purposes and daily activities including online payment transactions or e-banking. Thus, they are vulnerable to online fraud threats imposed by perpetrators. Developing cyber resilience will help them prepare for, adapt to, and recover from online fraud threats. In explaining the impact of perception, attitude, and behavior on cyber resilience towards online fraud threats among International Islamic University Malaysia (IIUM) students, this study utilizes social exchange theory (SET). SET helps provide an understanding of students' ability to keep their data secure and seek rewards for long-term benefits such as gaining extra knowledge on cyber-security as part of their preparation to handle stressful events imposed by perpetrators. The conceptual framework also assumes that during a stressful event imposed by perpetrators, students are likely to be more alert to the risk of becoming victims of online fraud. Therefore, the objective of this study is to identify the relationship between the main components of SET which are perception, attitude, and perception regarding cyber resiliency. A quantitative research design was employed in this study. The survey method was used, with a questionnaire as the instrument for data collection. A total of 269 undergraduate students from seven different Kulliyyah participated in this study. Findings show that there are significant relationships between perception, attitude, behavior, and cyber resilience towards online fraud. Thus, SET is supported in the study.